2011
DOI: 10.1002/clen.201100049
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pyridine from Aqueous Solution by Adsorption on an Activated Carbon Cloth

Abstract: Pyridine is a very toxic pollutant that has to be removed from wastewater. In this work, adsorption of pyridine on activated carbon cloth (ACC) is studied as a possible alternative for eliminating pyridine from aqueous solution. The ACC was produced from polyacrylonitrile. The adsorption equilibrium data of pyridine on ACC was obtained in a batch adsorber. The experimental data was interpreted with the isotherms of Langmuir, Freundlich, and Prausnitz-Radke (PR), and the PR isotherm better represented the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
1
7
0
5
Order By: Relevance
“…Many studies have explored pyridine adsorption performance using porous materials including activated carbons [9][10][11][12], clayey till and zeolites [13,14], synthetic apatite [1], polymer resins [15,16], and metal organic frameworks [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored pyridine adsorption performance using porous materials including activated carbons [9][10][11][12], clayey till and zeolites [13,14], synthetic apatite [1], polymer resins [15,16], and metal organic frameworks [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…U velikom broju radova opisan je uticaj mehaničke deformacije različitih vrsta materijala kako onih organskog porekla, tako i neorganskih, kojom je postignuta sinteza novih materijala i poboljšanje već postojećih osobina [2,6,15,16]. Sveobuhvatni pregled literature ukazuje na veliki broj metoda koje su korišćene za modifikaciju ugljenične tkanine: aktivacija kiselinama i bazama, oksidacija, modifikacija laserima [17][18][19][20][21][22]. Meñutim, nema podataka o primeni mehaničkog mlevenja na modifikaciju površine ugljenične tkanine.…”
Section: Uvodunclassified
“…Karboksilne, fenolne i laktonske ubrajaju se u kisele kiseonične grupe, dok su pironske, hinonske i druge grupe bazne (slika 1). Prisustvo i vrsta površinskih grupa odreñeno je vrstom početnog materijala (prekursora) od koga se ugljenični materijali dobijaju, procesa aktivacije ili posttretmanima u kojima se kiseonik, vodonik i dr. elementi uvode u strukturu [19][20][21][22]. U okviru ovog rada je ispitan uticaj mehaničkog mlevenja u različitim atmosferama (inertnoj i atmosferi vazduha) na broj i vrstu funkcionalnih grupa na površini tkanine.…”
Section: Uvodunclassified
See 1 more Smart Citation
“…In turn, it was found that intrafiber diffusion of the three latter compounds in ACC was reduced by hindered diffusion, which was explained by steric exclusion, drag effects, and obstruction due to molecules adsorbed on the pore walls. Furthermore, the effect of the solution pH and of the temperature on the adsorption of pyridine onto the same commercial PAN-based ACC was also recently examined [156]. The adsorption capacity of the ACC was found to increase by increasing the solution pH from 3 to 6, but it was almost independent of the temperature in the range investigated ∘ C).…”
Section: Isrn Chemical Engineeringmentioning
confidence: 99%